Navigating entrepreneurial intentions: The role of educational, family, and ecosystem support on willingness to take risks among Malaysian postgraduate students - Chan, Man Seong; Tan, Chi Hau; Mah, Pei Yew; Tan, Booi Chen (International Journal of Innovative Research and Scientific Studies, 2025)
In Malaysia, entrepreneurship among young people has garnered significant attention due to its substantial contributions to social and economic development in the nation. Young people are generally open to taking risks and exploring new entrepreneurial ventures, while the perspective of postgraduate students remains underexplored. Hence, based on the Social Cognitive Theory, this study aims to investigate the effects of entrepreneurship education, family, and ecosystem support on postgraduate students' risk-taking willingness in Malaysian higher education institutions. The study will also examine whether risk-taking willingness mediates the relationship between these support factors and entrepreneurial intention among postgraduate students. This study employed a quantitative approach, distributing online questionnaires to 227 postgraduate students at Malaysian universities. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), a two-step approach was followed: first assessing the measurement model and then examining the structural model to test the proposed hypotheses. The findings reveal that entrepreneurship education, family, and ecosystem support significantly influence risk-taking willingness. In addition, this study confirmed the mediating role of risk-taking willingness in enhancing entrepreneurial intention among postgraduate students in Malaysia. Lastly, both theoretical and managerial implications were discussed, and the research limitations and suggestions for future research directions were also put forward.